Amblyomma cajennense (Acari : Ixodidae): Salivary gland cells of partially engorged females ticks and the production of lipid by their mitochondria - Denardi, S. E.; Mathias, Maria Izabel Camargo [UNESP]; Bechara, G. H. (Elsevier B.V., 2006)
Morphologically,. The salivary glands of ticks are paired structures consisting of a secretory and an excretory portion, lacking a reservoir for the storage of the secretion. The secretory portion is composed in females by cells that form acini classified into the types I, II, and III. The excretory possess a major duct, from which arise several intermediate ducts that then subdivide to form the canaliculi or acinal tubules, which end at the acini from where they collect the secretion. The present Study describes the ultrastructural changes that occur in the mitochondria of cells of the acini I, II, and III in the salivary glands of partially engorged females of the Cayenne tick Amblyomma cajennense. The results show that this organelle exhibits completely disarrayed crests due to the presence of lipidic material inside the matrix and between the crests, thus demonstrating their participation in the production of the lipids that would be used structurally by the cells. These organelles with ultrastructural changes were denominated derived mitochondria. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: salivary gland; derived mitochondria; ultrastructure